Light-regulated and cell-specific methylation of the maize PEPC promoter - Tolley, Ben J (Journal of experimental botany, 2012)
The molecular mechanisms governing PEPC expression in maize remain to be fully defined. Differential methylation of a region in the PEPC promoter has been shown to correlate with transcript accumulation, however, to date, investigations into the role of DNA methylation in maize PEPC expression have relied on the use of methylation-sensitive restriction enzymes. Bisulphite sequencing was used here to provide a single-base resolution methylation map of the maize PEPC promoter. It is shown that four cytosine residues in the PEPC promoter are heavily methylated in maize root tissue. In leaves, de-methylation of these cytosines is dependent on illumination and is coincident with elevated PEPC expression. Furthermore, light-regulated de-methylation of these cytosines occurs only in mesophyll cells. No methylation was discovered in the 0.6 kb promoter required for mesophyll-specific expression indicating that cytosine methylation is not required to direct the cell-specificity of PEPC expression. This raises interesting questions regarding the function of the cell-specific cytosine de-methylation observed in the upstream region of the PEPC promoter